Foto-Foto Karya Kassian Céphas dalam Dialektika Sosial - Kusrini . (Rekam: Jurnal Fotografi, Televisi, Animasi)
Kassian Céphas is recognized as photographer Kraton Yogyakarta that has the equal rights of Europeans in the nineteenth century. Photographs of his work in addition to documentation of Yogyakarta and the Dutch empire, also sold as souvenirs for the Europeans. Although at that time the profession as a photographer is still scarce, but Céphas work professionally. Photographs by Céphas has recorded social and cultural development as part of the social dialectic. Attributes clothing, custom intergovernmental exchange visits, as well as efforts to obtain equal footing Céphas Europeans, showed a socio-cultural dialogue. Céphas works is a form of social description that has been cultured people of Yogyakarta, about art and knowledge though not necessarily a formal education. Through his photographs, Céphas confirms the existence ofYogyakarta as part of a nation.Keywords: Céphas, photographs, social dialectic, culture, nation.